Sejarah Gaya Desain Grafis Kover Album Piringan Hitam Musisi Indonesia Tahun 1961-1969 Koleksi Irama Nusantara - Sudjadi Tjipto R. (Institut Seni Indonesia Yogyakarta, 2019)
Abstract.Documentation of musical works in Indonesia has never been noticed by stakeholders (government) from the past to the present. The absence of agencies related to documenting Indonesian music works has caused the young generation to never know good quality domestic children's music. In the past music works were first produced in the form of vinyl or in Indonesia called “Piringan Hitam / PH”, then tapes, and finally on CD (Compact Disc). At the level of music lovers or collectors, Indonesian Music vinyl is the most sought-after music artifact, of high value due to the scarcity of its production. It is “interesting to look at the beauty of the style of vinyl records in the early recording industry in Indonesia at that time.This study would like to examine the history of the relationship between the style of design of the vinyl records in Indonesia in relation to the design style in America. Historical research methods used in the study of the style of art and design with research materials obtained from the observation of digital data (download) of the Irama Nusantara portal and literature studies from journal articles and related reference books. The results of the study showed that the relationship between vinyl design in Indonesia was influenced by the business relationship of the record label, the current design trend and the limitations of the cover designer / artist and the limitations of the printing technology at that time.Keywords: vinyl, design graphic, record label